Bony outgrowths in the stomatognathic system: clinical and sociodemographic characterization in a cross-sectional study - Tovío-Martínez, Eilien (2025)
Objectives: To clinically and sociodemographically characterize bony exostoses in the stomatognathic system, identifying their prevalence, anatomical distribution, and potential associated factors such as family history and oral parafunctional habits. Materials and Methods: A retrospective, descriptive, cross-sectional study was conducted using 178 medical records of patients treated between 2020 and 2024 at a private stomatology, oral and maxillofacial surgery practice in Medellín. Sociodemographic, anatomical, environmental variables, and family history were analyzed. Data collection was performed via a standardized form, followed by descriptive statistical analysis. Results: Eighty-three percent of patients were female and 17% male, with a mean age of 37 ± 3 years. Forty-five percent originated from the Andean region. Bony exostoses were predominantly located in the mandible (54.7%), followed by the palate (31.3%). The most common associated diagnosis was bruxism (47%). Eighty-one percent of patients reported a family history of bony exostoses. Primary reasons for surgical removal included aesthetic concerns (41%), prosthetic maladaptation (33%), and oral hygiene difficulty (16%). Conclusions: Bony exostoses in the stomatognathic system were more frequent in females and the mandibular region. An association with family history and parafunctional habits such as bruxism was observed, suggesting potential genetic and environmental predisposition. Further studies with a prospective design and genetic-nutritional analysis are required to explore these relationships in greater depth.